Perempuan Bima dan Strategi Adaptasi Pasca Bencana Banjir Bandang (Studi Kasus Peran Perempuan di Kabupaten Bima, NTB) - Ika Wijayanti; Oryza Pneumatica I; Siti Nurjannah (Universitas Trunojoyo Madura, 2018)
The research titled “Bima’s Women and Post Disaster Mitigation Adaption Strategy for flash floods (Case Study of Women in Maintaining family Economics After The Flash Floods Disaster in Bima)” Takes place in Nisa Village, Woha Subdistrict, Bima District. By doing this research, the researcher are expected to be able to: (1) knowing in depth the adaptive strategy done by women in reconstructing their social life after flash floods disaster, (2) knowing the change of life after flash floods, (3) knowing the obstacles faced by women in the implementation post flash floods adaptive strategy. This research uses explorative qualitative research method. The research location is located in Nisa Village, Woha District, Bima District, West Nusa Tenggara Province. The subjects of this study were women housewives and Nisa village apparatus. Data were collected through interviews and observations to collect information on adavtive strategies, changes in post-flash floods life, and the constraints faced by women in implementing adaptive strategies after the flash floods disaster. Further data analysis by performing several stages that include data collection, data classification, interpretation to the writing of research reports. The results of this research show that (i) Nisa village women experiencing changes in economic, social and cultural life after the disaster flash floods. (ii) adaptive strategies implemented by Nisa village women in sustaining their household economies, among others, by active strategies in the form of exploiting natural resources and human resources from close relatives, extending working hours, and working to reduce family economic expenditure. The network strategy undertaken by Nisa village women is by owing the banks and neighbors. (iii) the constraints faced by women in Nisa village in carrying out an effective strategy are the loss of some natural resources that can support economic recovery , large losses due to flood disaster become an obstacle in economic recovery, and lack of acces to village economic institutions.